Correlation Between Testosterone Level With HBA1C Level As Glycemic Control Marker Among Type 2 Diabetes Mellitus Patient - Halim, Fenny; Listiana, Devia Eka; Karlowee, Vega; Istiadi, Hermawan; Prasetyo, Awal; Astuti, Meira Dewi Kusuma (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Helicobacter pylori is classified as a grade 1 carcinogen by the International Agency for Research on Cancer. Identification of Helicobacter pylori infection is crucial for the prevention of malignancy. Immunohistochemistry is more specific and sensitive than modified Giemsa because it based on the antigen- antibody binding so it can exclude other organisms. However, it can be expressed in all species of Helicobacter genus. OBJECTIVE: To compare the identification methods of Helicobacter spp in stomach biopsy between modified Giemsa and immunohistochemistry. METHOD: This research was a cross-sectional study. There were 64 biopsies taken by simple random sampling. They consisted of 32 positive and 32 negative Helicobacter spp based on the interpretation of modified Giemsa. Statistical analysis using x2 test. RESULT: The number of atypical Helicobacter spp was 42.%. The number of samples that received Proton Pump Inhibitor (PPI) therapy was 93.75%. Helicobacter spp was positive in 31 samples and negative in 33 samples based on the interpretation of immunohistochemistry staining. There was no significant difference (p=0.617) between the identification results of Helicobacter spp using immunohistochemistry compared to the Modified Giemsa at both 400x and 1000x magnification. CONCLUSION: Modified Giemsa is still reliable for identifying Helicobacter spp, especially in classical form, compared to immunohistochemistry. Due to the administration of PPI, there are a lot of cases with atypical form of Helicobacter spp which can be differentiated into coccoid form and intraepithelial located. Immunohistochemistry staining is useful in identify these cases.